The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s13311-013-0255-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment with 17-DMAG Improves Balance and Coordination in A New Mouse Model of Machado-Joseph Disease

Abstract: Machado-Joseph disease (MJD) or spinocerebellar ataxia type 3 (SCA3) is a neurodegenerative disease currently with no treatment. We describe a novel mouse model of MJD which expresses mutant human ataxin-3 at near endogenous levels and manifests MJD-like motor symptoms that appear gradually and progress over time. CMVMJD135 mice show ataxin-3 intranuclear inclusions in the CNS and neurodegenerative changes in key disease regions, such as the pontine and dentate nuclei. Hsp90 inhibition has shown promising outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
174
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(191 citation statements)
references
References 51 publications
13
174
0
Order By: Relevance
“…However, the mechanism underlying the formation of these inclusions is still poorly understood because of the lack of an appropriate model [10, 20]. Recent studies reported a novel mouse model of SCA3 that could be used to study the pathogenesis and treatment of SCA3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism underlying the formation of these inclusions is still poorly understood because of the lack of an appropriate model [10, 20]. Recent studies reported a novel mouse model of SCA3 that could be used to study the pathogenesis and treatment of SCA3.…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with our in vitro neuronal differentiation of SCA3-iPS cells. Growing evidence has revealed that regulation of autophagy is involved in many human diseases, including neurodegeneration [8, 20]. Aggregation of the mutated form of the disease protein ATXN3 into neuronal nuclear inclusions has been studied extensively in SCA3.…”
Section: Discussionmentioning
confidence: 99%
“…Infrared beams were used to automatically register animals’ movements. We next monitored forelimb strength, hindlimb tonus, hindlimb clasping, negative geotaxis, and gait analysis as previously described (Silva‐Fernandes et al ., 2014). For all tests, scoring was carried out manually by an experimenter blind to the genotype and age of the animals.…”
Section: Methodsmentioning
confidence: 99%
“…In SCA3 mice, Hsp90 inhibition with 17-DMAG improved motor function, while decreasing mutant ataxin-3 aggregation and levels, possibly via autophagy activation since 17-DMAG treatment increased both beclin-1 and LC3-II levels [209].…”
Section: Pharmacological Modulation Of Molecular Chaperones In Scas Amentioning
confidence: 95%